The Effect of Educational Computer Games on Learning, Retention and Academic Achievement Motivation among Female Students with Intellectual Disability - Elaheh Velayati; Esmail Zaraii Zavaraki; Mohammah Hasan Amirteimouri (Ravānshināsī-i Afrād-i Istis̠nāyī, 2013)
The aim of this study is to evaluate the impact of educational computer games on learning, retention and academic achievement motivationof elementary mathematical concepts among mentally retarded students. This study quasi-experimental study uses a design with pre-test and post-test with the control group. In this study, the statistical population consists of all the 2nd grade female mentally retarded students in the exceptional education schools in Tehran in the academic year of 2011-2012. Using the convenient sampling method, an exceptional school located in District 15 of Tehran is selected for this research. Learning and academic achievement motivation pre-tests is performed in both experimental and control groups. In the experimental group, first the teacher taught the adding concept completely to students and used computer games as exercise for the taught concept. However, the teacher in the control group continued its traditional method of teaching the concept. Then, learning and academic achievement motivation post-tests is performed in both experimental and control groups. The retention test is administered two weeks after the learning test. The data obtained about the first and third hypothesis are analyzed using an independent T test and the data obtained about the second hypothesis are analyzed using the T test difference scores. Results show that the mathematical educational computer games increase learning and academic achievement motivation in students with intellectual disability as regards the addition concept. However, it does not increase the retention ability in them.